2021
DOI: 10.1007/s00344-021-10446-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nitric Oxide in Conferring Multiple Abiotic Stress Tolerance in Plants and Crosstalk with Other Plant Growth Regulators

Abstract: Nitric oxide (NO) is a free-radical gasotransmitter signaling molecule associated with a varied spectrum of signal transduction pathways linked to inducing cross-adaptation against abiotic stresses. It has crucial roles from seed germination to plant maturity, depending upon its cellular concentration. The functional cross-talk of NO among different stress signaling cascades leads to alteration in the expression of developmental genes that regulate biosynthesis and function of plant growth regulators (PGRs). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 225 publications
(213 reference statements)
0
20
0
1
Order By: Relevance
“…Abiotic stress affects photosynthesis in higher plants by targeting the photosynthetic apparatus, particularly photosystem (PS) II (1,2). A common consequence of abiotic/biotic stress is the increase in both reactive oxygen species (ROS) and nitric oxide (NO) levels in plant cells (3,4). ROS and NO could exert multiple effects on photosynthetic and mitochondrial metabolisms (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic stress affects photosynthesis in higher plants by targeting the photosynthetic apparatus, particularly photosystem (PS) II (1,2). A common consequence of abiotic/biotic stress is the increase in both reactive oxygen species (ROS) and nitric oxide (NO) levels in plant cells (3,4). ROS and NO could exert multiple effects on photosynthetic and mitochondrial metabolisms (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…NO-derived molecules, also known as reactive nitrogen species (RNS), play key roles in maintaining the intracellular redox homeostasis and signaling for the activation of antioxidant mechanisms. It has been reported that the application of NO in plants under stressful conditions helps protect the growth, photosynthesis, and enzyme activity by upregulating the tolerance mechanisms ( Fatma et al., 2016 ; Nabi et al., 2019 ; Singhal et al., 2021 ). Recently, in Hordeum vulgare L., the application of NO has been reported to alleviate the damaging effects of copper on plant growth and photosynthesis by upregulating the antioxidant function and maintaining the redox homeostasis ( Massoud et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The promptness of the response depends on the number of neurons connecting the stimuli. In plants, the repertoire of secondary messengers, i.e., ROS, Ca 2+ , NO, SA, JA and pipecolic acid, plays a crucial role in memory response [ 83 , 84 , 85 , 86 ]. Short-term memory is not always associated with transcriptional reprogramming in both plants and animals.…”
Section: Priming Vs Memory and The Fine Line Of The Differencementioning
confidence: 99%